UPAYA PENINGKATAN MOTIVASI BELAJAR ANAK KELOMPOK A MELALUI PEMBELAJARAN KOGNITIF DENGAN METODE BERMAIN BALOK DI RA MIFTAHUL HUDA TAJINAN MALANG - Rina Wahyu Hidayati; Rosichin Mansur; Ika Anggraheni (UNISMA, 2020)
This research is motivated by the lack of maximum learning motivation of children in cognitive learning in RA Miftahul Huda Tajinan. Children with complete criteria in increasing cognitive learning motivation just only 50%. This study aims to describe the application of the beam playing method in increasing cognitive learning motivation in early childhood group A in RA Miftahul Huda Tajinan and describing the application of the beam playing method can increase cognitive learning motivation in early childhood group A in RA Miftahul Huda Tajinan Malang.The method used is classroom action research, with a model developed by Kemmis and Taggart in one cycle there are four stages namely planning, implementing, observing, and reflecting. One cycle was carried out a day with the subjects of the study being 20 children of group A (9 boys and 11 girls) in RA Miftahul Huda Malang. For data collection techniques using 3 methods, namely the method of observation (data collection is done alone and assisted by the class teacher), the documentation method (in the form of RPPH, assessment books, absences book, photos), the method of interviews with group A teachers. The research instrument used is the documentation used. in the form of children's learning outcomes, assessment books, observation sheets and interview guidelines. Data analysis techniques use 4 stages, namely data reduction (summarizing the data in chapter IV), data presentation (data summarized in the form of analyzed reports), data verification, and data conclusions to facilitate checking the validity of the data (consisting of persistence of observations, triangulation, peer checking). The results of this study indicate an increase in children learning motivation through cognitive learning with the beam playing method . This is evidenced by the average value of the percentage of children's cognitive learning abilities at the time of pre-cycle 50% of the number of children who completed 10 children. In cycle I obtained an average value of 65% with the total number of children who finished 13 children. And the results of the average percentage of the second cycle of 90% with the number of children who finished 18 children. The average value of the percentage of children from cycle I to cycle II has increased. The average value of completeness percentage of group A children in RA Miftahul Huda Tajinan Malang through cognitive learning using the beam playing method is 50% in the pre cycle, 65% in cycle I, and by 90% in cycle II.